Studies on Solid Solutions of Hydroxyl Apatite of Calcium and Some Micronutrient Metals - Rao, T.V.R.K.; Choudhary, V.K. (Asian Journal of Chemistry, 2010)
Formation of solid solutions of hydroxyl apatites of calcium and some micronutrient metal ions viz., Mn2+, Fe2+, Ni2+, Cu2+ or Zn2+ has been studied. Solid solutions of composition, Ca7M3(PO4)6(OH)2 and Ca5M5(PO4)6(OH)2 (where M = micronutrient metal) were prepared by co-precipitation method. Solid solutions were characterized by analytical studies. The molar g-atom ratio (Ca + M)/P was found to be closer to the theoretical value for hydroxyl apatites suggesting their homogeneity. X-ray diffraction studies showed the decrease of lattice parameter values and contraction of unit cell volume consequent upon substitution of micronutrient metal ion into the calcium hydroxyl apatite suggesting the formation of homogeneous solid solutions. Infrared spectra of solid solutions suggested a coordinated mode of phosphate. Covalence of cation-phosphate bonding seem to increase with the induction of trace metal ion to the apatite. Spectra further suggested the OH of solid solutions to be hydrogen bonded. Implications of the results in phosphate urolithology have been discussed.